Difficulties in interpreting and translating Russian adjectives into Arabic, based on the novel "Smoke" by I. S. Turgenev - Dr. Faris Hassoon Ali; Dr. Hussein Kazem Majdi (Journal of College of Education, 2026)
Annotation :This article is devoted to the analytical translation of the contiguous in the Russian fiction work of the Russian writer I. S. Turgenev “Smoke” translated by Shukri Mohammed Ayyad and explains the semantic meanings of contiguous which are acquired in Arabic translation. Translation is an important means of interaction between people speaking different languages and contributes to the enrichment of national literatures.
Keywords: : semantics, adjectives; interpretations; Arabic translation; Russian literary productions.